2016
DOI: 10.1007/s00296-016-3458-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of progranulin in patients with lupus nephritis and its correlation with disease activity

Abstract: The aim of this study was to explore whether progranulin (PGRN) can be a useful marker not only for accurate diagnosis of patients with active lupus nephritis (LN), but also for prediction of the disease activity in this population. A total of 154 LN patients were enrolled in this study, 76 of which were diagnosed as having active LN and 78 as having stable LN. Additionally, 71 age-matched non-LN patients were enrolled as controls. The serum and urine PGRN levels of each study population were measured using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Moreover, there was no significant difference between PGRN and IGFBP-2 and classes of renal biopsy. For PGRN, our results were consistent with those of Tanaka et al [13] and Wu et al [14]. For IGFBP-2, our results agreed with those of Ding et al [10].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, there was no significant difference between PGRN and IGFBP-2 and classes of renal biopsy. For PGRN, our results were consistent with those of Tanaka et al [13] and Wu et al [14]. For IGFBP-2, our results agreed with those of Ding et al [10].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed a significant difference between the 3 groups with respect to PGRN and IGFBP-2, except for ILGFBP-2, where no significant difference was noted between the CKD and control groups. These findings agreed with the findings of some studies on PGRN [14,34]. Tanaka et al [13] also found higher levels of PGRN in SLE patients than in controls.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations